Social networking sites use and life satisfaction: a moderated mediation model of e-health literacy, fatigue, uncertainty, and stress - Saeed Pahlevan Sharif; Navaz Naghavi; Osveh Esmaeelinezhad; Long She; Kelly-Ann Allen; Hamid Sharif-Nia; Pardis Rahmatpour (BMC Psychology)
Abstract Excessive social media use during health crises can lead to information overload and psychological distress, yet the mechanisms underlying this relationship remain unclear. This study investigated how social networking sites (SNS) affected life satisfaction during the COVID-19 pandemic in Iran and whether this relationship was explained by SNS fatigue, uncertainty about disease, and stress. The research also examined whether e-health literacy was a protective factor in this process. Results confirmed that SNS use negatively affected life satisfaction through a sequential pathway of increased fatigue, uncertainty, and stress. E-health literacy moderated the initial link between SNS use and fatigue, with higher literacy weakening this relationship. The results demonstrate the complex relationship between SNS use and wellbeing during health crises and highlight the potential protective role of e-health literacy.